LITERATURE REVIEW IRREGULAR MENSTRUAL CYCLE BASED ON BMI AND BODY FAT PERCENTAGE - Nurul Hikma; Zakiyatul Faizah; Rize Budi Amalia (Indonesian Midwifery and Health Sciences Journal, 2021)
AbstractBackground: The menstrual cycle can be said to be normal if the interval is between 21-35 days. The prevalence rates associated with menstrual cycle disorders were found in the range of 15.8-89.5. Nutritional status is one of the factors that cause menstrual cycle disorders, where nutritional status can be determined using body mass index and measuring the percentage of fat in the body. The purpose of this study was to determine the relationship between nutritional status and the menstrual cycle using the literature review method. The formulation of the problem in this research is determined by PICO, namely: "is there a relationship between nutritional status and menstrual cycle disorders?". A total of 749 literary works obtained from the Google Scholar, Science Direct, PubMed and ProQuest databases were used as a literature review source, where in screening the literature the inclusion and exclusion criteria were seen, which had previously been determined so that finally six literatures were reviewed. Results: The cause of menstrual cycle disorders has been found in adolescents with an average value of 18.4-37.8 and the percentage of body fat between 12.80-34.80. Conclusion: Based on all literature that has been reviewed, it can be concluded that menstrual cycle disorders have a significant relationship with body mass index and body fat percentage.